Effect of long time Moulting Mud Crab (Syclla serrata) Males With Popey Methods and Methods Ablation In Cot Gampong Lamkuweh Meuraxa district of Banda Aceh - Sabrina Ayu Nani Nasution; Muhammad Ali Sarong; Ismul Huda (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Mangrove crabs are soft shell crab molting phase Bakau (molting). Molting process in nature occurs varies with different methods that need to be done penelitian.Tujuan this research is to know the effect of cutting the foot of the street (popey) and the binding of the eyeball (ablation) to long time Bakau molting crab (Scylla serrata) male in Gampong Cot Lamkuweh Meuraxa district of Banda Aceh. The work was undertaken in April-November 2016. The method used in the cultivation process is the soft shell crab Mangrove foot path method (popey), the binding of the eyeball (ablation) and natural implemented in Gampong Cot Lamkuweh Meuraxa district of Banda Aceh. Processing data using Variant Analysis (ANOVA). The degree of survival for all treatments ranged between 60% -75%. The growth rate of the highest daily weight contained in the binding of the eyeball treatment (ablation) that is equal to 48.91%. While the number of crab molting within 40 days of the highest in the treatment of leg amputation (popey) of mangrove crab molting on day 21 until day 3. Crab molting against time ranged WiBB 20:00 - 22:00 WiBB and only a few crabs molting in the morning and afternoon. The conclusion states that the soft shell mud crab no significant effect on the degree of survival and the growth rate of daily weight (P 0.05) but significant effect on the day and time of molting mud crab. Key Words: Effect of Molting, Popey, Ablation, Mud Crab